Clavulanic acid production by immobilized cells of Streptomyces clavuligerus - Lavarda, Susana Cristina Sperandei [UNESP]; Hokka, Carlos Osamu; Araujo, Maria Lucia Gonsales Da Costa [UNESP] (My University, 2006)
A clavulanic acid production process with immobilized Streptomyces clavuligerus cells was investigated. Cells were immobilized in diatomaceous earth, calcium alginate gel as well as in the form of natural pellets and cultivated in shake flasks in a medium containing glycerol and soytone as the carbon and nitrogen sources, respectively. In all experiments growth occurred in the first 48 h and glycerol consumption after 72 h, while clavulanic acid production was observed between 48 and 60h, with gradual degradation after this period. The natural pellets presented higher product concentration as compared with the cells immobilized in supports. However, calcium alginate was found to be the best support in relation to cell retention capacity.
Keywords: Alginate calcium gel; Celite; Immobilization cells; Pellets; Streptomyces clavuligerus